Additive manufacturing of electrochemical interfaces : simultaneous detection of biomarkers - Ho, Eugene Hong Zhuang (2019)
3D-printed stainless steel helical shaped electrodes with or without surface modification with a gold (Au) film are tested as novel electrode materials for the electrochemical detection of ascorbic acid and uric acid in aqueous solutions. Their performance in terms of sensitivity, selectivity and reproducibility is evaluated and compared to conventional glassy carbon electrode (GCE). Owing to the excellent electrocatalytic properties of the 3D-printed gold (Au) electrode, a clear separation between the anodic oxidation signal of ascorbic acid and uric acid in differential pulse voltammogram (DPV) could be obtained, allowing simultaneous quantification of these biomarkers. The oxidation current obtained using the 3D-printed Au electrode increased linearly with its respective biomarkers concentration in the range of 0.1–1 mM. Furthermore, the 3D-printed Au electrode generally performed better in terms of sensitivity and detection limits as compared to GCE. A real sample analysis of Vitamin C tablet (500 mg), Vitacimin was conducted using the 3D-printed Au electrode obtaining a variation from claimed concentration of ascorbic acid of only about 0.5%. Therefore, electrodes fabricated by 3D printing would certainly represent a viable alternative to conventional electrodes for efficient electrochemical analysis in the future.